Hypoventilation training including maximal end-expiratory breath holding improves the ability to repeat high-intensity efforts in elite judo athletes - Woorons, X.; Faucher, C.; Dufour, S. P.; Brocherie, F.; Robach, P.; Connes, P.; Brugniaux, J. V.; Verges, S.; Gaston, A. F.; Millet, G.; Dupuy, O.; Pichon, A. (Frontiers in Physiology, 2024)
Purpose: To investigate the effects of a repeated-sprint training in hypoxia induced by voluntary hypoventilation at low lung volume (RSH-VHL) including end-expiratory breath holding (EEBH) of maximal duration.Methods: Over a 4-week period, twenty elite judo athletes (10 women and 10 men) were randomly split into two groups to perform 8 sessions of rowing repeated-sprint exercise either with RSH-VHL (each sprint with maximal EEBH) or with unrestricted breathing (RSN, 10-s sprints). Before (Pre-), five days after (Post-1) and twelve days after (Post-2) the last training session, participants completed a repeated-sprint ability (RSA) test on a rowing ergometer (8×25-s "all-out" repetitions interspersed with 25 s of passive recovery). Power output (PO), oxygen uptake, perceptual-motor capacity (turning off a traffic light with a predetermined code), cerebral (Δ[Hbdiff]) and muscle (Δ[Hb/Mb]diff) oxygenation, cerebral total haemoglobin concentration (Δ[THb]) and muscle total haemoglobin/myoglobin concentration (Δ[THb/Mb]) were measured during each RSA repetition and/or recovery period. Results: From Pre-to Post-1 and Post-2, maximal PO, mean PO (MPO) of the first half of the test (repetitions 1-4), oxygen uptake, end-repetition cerebral Δ[Hbdiff] and Δ[THb], end-repetition muscle Δ[Hb/Mb]diff and Δ[THb/Mb] and perceptual-motor capacity remained unchanged in both groups.Conversely, MPO of the second half of the test (repetitions 5-8) was higher at Post-1 than at Pre-in RSH-VHL only (p<0.01), resulting in a lower percentage decrement score over the entire RSA test (20.4 ± 6.5 vs. 23.9 ± 7.0%, p=0.01). Furthermore, MPO(5-8) was greater in RSH-VHL than in RSN at Post-1 (p=0.04). These performance results were accompanied by an increase in muscle Δ[THb/Mb] (p<0.01) and a concomitant decrease in cerebral Δ[THb] (p<0.01) during the recovery periods of the RSA test at Post-1 in RSH-VHL.Four weeks of RSH-VHL including maximal EEBH improved the ability of elite judo athletes to repeat high-intensity efforts. The performance improvement, observed 5 days but not 12 days after training, may be due to enhanced muscle perfusion. The unchanged oxygen uptake and the decrease in cerebral regional blood volume observed at the same time suggest that a blood volume redistribution occurred after the RSH-VHL intervention to meet the increase in muscle perfusion.